2020
DOI: 10.1075/ssol.20002.nic
|View full text |Cite
|
Sign up to set email alerts
|

Science fiction prototyping’s features and impact on college students’ perceptions of writing

Abstract: The present study develops an applied literariness study by exploring both the features, and the impact, of science fiction prototyping (SFP) on college students’ perceptions of disciplinary, or field-specific, writing. College students (N = 83), who were English (n = 35) or STEM (science, technology, engineering, mathematics) majors (n = 48), composed micro-science fiction prototyping (µSFP), a genre that blends creative and science writing. Linguistic Inquiry and Word Count (LIWC2015) analysis demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…At the same time, disciplinary writing framed as a WID experience that socializes students into disciplinary ways of thinking may then help students develop declarative knowledge about writing genres as responses to recurring social exigencies or needs. Educators may especially be able to leverage the reflective power of journaling as a WTL experience and the WID experience of such imaginative writing that is used in industry, such as science fiction prototyping (Nicholes, 2018(Nicholes, , 2020, to give students chances to demonstrate how creative narratives lie within scientific-discourse boundaries. Participants in this study, as noted above, may have found value in more explicitly overlaying science writing with creative and personal writing.…”
Section: Finding 4: Chemistry Majors and Creative Writingmentioning
confidence: 99%
“…At the same time, disciplinary writing framed as a WID experience that socializes students into disciplinary ways of thinking may then help students develop declarative knowledge about writing genres as responses to recurring social exigencies or needs. Educators may especially be able to leverage the reflective power of journaling as a WTL experience and the WID experience of such imaginative writing that is used in industry, such as science fiction prototyping (Nicholes, 2018(Nicholes, , 2020, to give students chances to demonstrate how creative narratives lie within scientific-discourse boundaries. Participants in this study, as noted above, may have found value in more explicitly overlaying science writing with creative and personal writing.…”
Section: Finding 4: Chemistry Majors and Creative Writingmentioning
confidence: 99%